Affective map of Warsaw: Testing Alexander’s pattern language theory in an urban landscape - Iwańczak, Bartłomiej; Lewicka, Maria (Landscape and urban planning, 2020)
•Presence of Alexander’s patterns in an urban landscape was associated with positive affect.•The patterns were associated mostly with the emotion of relaxation.•Pattern theory is a manifestation of the conservative rather than the progressive place meaning.•With the exception of the downtown, Warsaw was judged as relaxing and relatively boring. A pattern language is a set of recipes, described by the architect Christopher Alexander, to help design spaces that will appeal to everybody and satisfy basic human needs. In this paper, we tested (1) whether the presence of patterns in an urban landscape is associated with a positive affect and aesthetic appreciation, and (2) what kind of emotions (low or high arousal) are elicited by settings with identified patterns and thus whether pattern theory is a manifestation of the conservative (enclosed, with continuous identity and offering rest) or the progressive (open, dynamic, and promoting social interaction) meaning of place. Participants evaluated 1310 panoramic pictures covering the entire area of a large European city (Warsaw), according to the four types of elicited affect (relaxation, excitement, irritation, and boredom), aesthetics (pretty vs. ugly settings), and liking. Expert judges estimated the presence of 68 patterns in the same pictures. The findings show that the presence of patterns in an urban landscape was associated with increased positive affect, aesthetic appreciation of the setting, and more liking. The effects of the presence of patterns were not eliminated by the content of the pictures (e.g., the presence or lack of nature). The dominant emotion was that of relaxation, suggesting that pattern language theory is rooted in the conservative (essentialist) rather than the progressive (anti-essentialist) concept of place. Except for the strictly defined downtown, Warsaw was judged as a mostly relaxed, and somewhat boring city. Alternative explanations and suggestions for future studies have been presented.